Effect of Annealing on the Optical Properties of Transition Metal Doped ZnO Thin Films. Issue 1 (17th February 2015) - Mathew, Jijoy P; Varghese, George; Mathew, Jacob
Abstract: A group of transition metal (Co, Cu, Ni) doped ZnO thin films were prepared by a low cost dip coating method. To study the effect of annealing temperature on the structural and optical properties of the grown films each film is subjected to three different annealing temperatures. From the calculation of structural parameters from the XRD spectrum, it was found that each film possesses a tensile strain and this tensile strain increases as the annealing temperature increases. This dominant behavior of tensile strain affects the optical properties of the grown film in a greater extent.